Legal review of selling land of inheritence without approval of all heirs - Firmansa, Fakhrizal Arief; Anggraeny, Isdian; Pramithasari, Yelita Putri (Legality : Jurnal Ilmiah Hukum, 2020)
The land is one of the most valuable items because it is a source of life and livelihood for humans. The land has economic value and spiritual value for the owner. However, as the community's need for land increases, so does the legal problem in acquiring land. Everyone will disagree with one another in defending their land rights. One of them is ownership disputes that occur in inherited land which are the object of the transfer of land rights to other parties, for example through buying and selling. There are several phenomena of legal problems due to the sale and purchase of inherited land which is carried out unilaterally by one of the heirs and / or several heirs. Therefore, in this paper, we will discuss some problem formulations, namely: (1) What is the position of the sale and purchase of land over inherited land without the consent of all heirs? (2) What are the legal consequences of buying and selling land on inherited land without the consent of all heirs? Through normative juridical study, the following results are obtained. First, the legal act of buying and selling inherited land without the consent of all heirs is an illegal act before the law. Secondly, the legal consequences of buying and selling land on inherited land without the approval of all heirs are null and void.